Answer:
x = 7/13, y = 8/26
Explanation:
3x-2y=1 ...Equation 1 -2x+3y=2 ...Equation 2 Solve this equation.
3x - 2y =>1.....Equation 1
2x + 3y => 2......Equation 2
We solve using Elimination
We multiply Equation 1 by 3 and Equation 2 by 2 to Eliminate y
9x - 6y => 3.....Equation 4
4x + 6y => 4.......Equation 5
We Add Equation 4 and 5
13x = 7
x = 7/13
We substitute 7/13 for x in Equation 1
3x - 2y =>1.....Equation 1
3(7/13) - 2y => 1
21/13 - 2y = 1
21/13 - 1 = 2y
y =>21/13 - 1/2
y => 8/13 ÷ 2
y = 8/13 × 1/2
y = 8/26